2020
DOI: 10.1111/irv.12726
|View full text |Cite
|
Sign up to set email alerts
|

Human respiratory syncytial virus and influenza seasonality patterns—Early findings from the WHO global respiratory syncytial virus surveillance

Abstract: Wenqing Zhang 2 | On behalf of the WHO RSV Surveillance Group This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 23 publications
4
68
0
2
Order By: Relevance
“…For example, in Vietnam, a country with a tropical monsoon climate with high humidity, studies have found seasonal peaks of IAV during April to June [ 30 ], while in our study IAV peaked during December to January. In Egypt, a recent study showed that HRSV activity started in early winter and finished in early spring, similar to our findings, and found distinct annual peaks of HRSV that varied in duration and magnitude across the six tropical and subtropical countries included in their analysis [ 39 ]. They also found variation among participant countries regarding the timing of the peaks for influenza viruses and HRSV.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For example, in Vietnam, a country with a tropical monsoon climate with high humidity, studies have found seasonal peaks of IAV during April to June [ 30 ], while in our study IAV peaked during December to January. In Egypt, a recent study showed that HRSV activity started in early winter and finished in early spring, similar to our findings, and found distinct annual peaks of HRSV that varied in duration and magnitude across the six tropical and subtropical countries included in their analysis [ 39 ]. They also found variation among participant countries regarding the timing of the peaks for influenza viruses and HRSV.…”
Section: Discussionsupporting
confidence: 89%
“…In temperate zones, IAV, IAB and HRSV have very well-defined seasonality, being considered winter viruses, while AdV, HMPV, and PIV viruses circulate all year round with specific peaks for AdV subtypes in the fall (AdV1) and the spring-summer (AdV3) [ 32 , 39 , 40 ]. In our study, respiratory infections among pediatric participants generally peaked in the winter months, with IAV and IBV, HRSV, and AdV contributing the most to the overall infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regions with temperate climate, incidence of RSV infection concentrates during the winter months and may sometimes be absent in summertime 5 . In sub-tropical and tropical regions, RSV infection may be sporadic throughout the year or showed increased activity during the rainy or cooler months 6 .…”
mentioning
confidence: 99%
“…In temperate regions, an increase in influenza, respiratory syncytial virus (RSV) and seasonal CoV activities has been associated with cold and dry winters. In contrast, in the tropical and subtropical regions, epidemics uses to occur in rainy seasons or along the year [74,75,[81][82][83][84][85][86][87][88][89]. Time series analyses suggest that the likelihood of airborne transmission is favored by the presence of low relative humidity and lower temperature conditions [90][91][92].…”
Section: Sars-cov-2 and The Climatementioning
confidence: 99%